Travellers’ top comments during the COVID-19 pandemic in Botswana - Delly M. Chatibura (Research in Hospitality Management, 2020)
This article is an appraisal of the ongoing COVID-19 pandemic in Botswana. The article outlines literature in the context of impacts and reactions to the pandemic. The rest of the article builds upon the comments retrieved from TripAdvisor as the pandemic unfolds. Using text mining, a rapid assessment of travellers’ reflections of the pandemic on TripAdvisor is provided. The findings demonstrate the limited use of themes such as fear and anxiety or trip disruptions that can be associated with the pandemic, among travellers, who had stayed at varied accommodation facilities in the country. Instead, most of the travellers provided compliments, recommendations and revisit intentions, gave narrations of their trip experiences, game viewing and hunting experiences and were impressed with the location and overall appeal of the facilities. Such findings to some extent allay the uncertainties associated with travel in the country during the pandemic. The findings also emphasise the importance of accommodation facility attributes such as location, even during a crisis.